2011
DOI: 10.1002/ptr.3611
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Bacoside Extract fromBacopa monnieraon Physical Fatigue Induced by Forced Swimming

Abstract: The antifatigue effect of bacoside extract (BME) from Bacopa monniera (L.) Wettst. was investigated. Rats were subjected to weight-loaded forced swim test (WFST) every alternate day for 3 weeks. The BME at a dosage of 10 mg/kg body weight was administered orally to rats for 2 weeks in order to evaluate the following biomarkers of physical fatigue: swimming time, change in body weight, lipid peroxidation, lactic acid (LA), glycogen, antioxidant enzyme activities such as superoxide dismutase (SOD) and catalase (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
40
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 51 publications
(48 citation statements)
references
References 36 publications
7
40
0
Order By: Relevance
“…Antioxidants may be involved in glycogen metabolism so as to meet the energy requirements of working skeletal muscles and may act by terminating the chain reaction of lipid peroxidation so as to maintain the morphological stability of mitochondria in spinal motor neurons (Yu et al 2006). In our previous study, we have clearly shown that bacoside rich extract reduced the exercise-induced oxidative damage by inhibiting lipid peroxidation and enhancing the antioxidant defense by elevating the activities of antioxidant enzymes (Anand et al 2012). Effect of BRJ on lipid peroxidation, glycogen and lactic acid levels Swimming exercise significantly increased MDA level in muscle, liver and brain in control group compared to that of sedentary group.…”
Section: Effect Of Brj On Swimming Performancementioning
confidence: 89%
See 4 more Smart Citations
“…Antioxidants may be involved in glycogen metabolism so as to meet the energy requirements of working skeletal muscles and may act by terminating the chain reaction of lipid peroxidation so as to maintain the morphological stability of mitochondria in spinal motor neurons (Yu et al 2006). In our previous study, we have clearly shown that bacoside rich extract reduced the exercise-induced oxidative damage by inhibiting lipid peroxidation and enhancing the antioxidant defense by elevating the activities of antioxidant enzymes (Anand et al 2012). Effect of BRJ on lipid peroxidation, glycogen and lactic acid levels Swimming exercise significantly increased MDA level in muscle, liver and brain in control group compared to that of sedentary group.…”
Section: Effect Of Brj On Swimming Performancementioning
confidence: 89%
“…In our earlier studies we have demonstrated the physical endurance capacity of bacoside rich extract in rats (Anand et al 2012). Since, the bacoside rich extract is bitter in taste.…”
Section: Introductionmentioning
confidence: 88%
See 3 more Smart Citations